New approach to increasing rice lodging resistance and biomass yield through the use of high gibberellin producing varieties. - Ayako Okuno; Ko Hirano; Kenji Asano; Wakana Takase; Reiko Masuda; Yoichi Morinaka; Miyako Ueguchi-Tanaka; Hidemi Kitano; Makoto Matsuoka (PLoS ONE, 2014)
Traditional breeding for high-yielding rice has been dependent on the widespread use of fertilizers and the cultivation of gibberellin (GA)-deficient semi-dwarf varieties. The use of semi-dwarf plants facilitates high grain yield since these varieties possess high levels of lodging resistance, and thus could support the high grain weight. Although this approach has been successful in increasing grain yield, it is desirable to further improve grain production and also to breed for high biomass. In this study, we re-examined the effect of GA on rice lodging resistance and biomass yield using several GA-deficient mutants (e.g. having defects in the biosynthesis or perception of GA), and high-GA producing line or mutant. GA-deficient mutants displayed improved bending-type lodging resistance due to their short stature; however they showed reduced breaking-type lodging resistance and reduced total biomass. In plants producing high amounts of GA, the bending-type lodging resistance was inferior to the original cultivars. The breaking-type lodging resistance was improved due to increased lignin accumulation and/or larger culm diameters. Further, these lines had an increase in total biomass weight. These results show that the use of rice cultivars producing high levels of GA would be a novel approach to create higher lodging resistance and biomass.